I Remember Jazz : Six Decades Among the Great Jazzmen - Rose, Al (Book collections on Project MUSE., 1987)
Al Rose has known virtually every noteworthy jazz musician of this century. For many of them he has organized concerts, composed songs that they later played or sang, and promoted their acts. He has, when called upon, bailed them out of jail, straightened out their finances, stood up for them at their weddings, and eulogized them at their funerals. He has caroused with them in bars and clubs from New Orleans to New York, from Paris to Singapore-and survived to tell the story. The result has been a lifetime of friendship with some of the music world's most engaging and rambunctious personalitie.